Color stability of steaks from carcasses vascularly infused immediately after exsanguination - Melvin C. Hunt; J.J. Schoenbeck; T.E. Dobbels; Michael E. Dikeman; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 1999)
Hereford x Angus carcasses were infused with a solution of either sugar/phosphate or calcium chloride immediately after exsanguination to determine effects on color stability during retail display. A calcium chloride solution darkened the cuts and reduced color stability. A sugar/phosphate blend made steaks appear lighter red (more desirable), and their color stability was equal to that of the noninfused control.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Infusion; Display; Color stability